Unusual method for phenolic hydroxyl bridged lanthanide CPs: Syntheses, characterization, one and two photon luminescence - Zeng, Cheng-Hui; Zhao, Fu-Li; Yang, Yang-Yi; Xie, Ming-Yuan; Ding, Xue-Mei; Hou, De-Jian; Ng, Seik Weng (Royal Society of Chemistry, 2013)
A "basophilic method" for phenolic hydroxyl bridged lanthanide coordination polymers (CPs) was developed. With this method, eleven CPs with the general formula of [Ln(HL1)L1·H2O]n (Ln = Tb (1), Nd (2), Eu (3), Gd (4), La (5), Er (6), Y (7), H2L1 = 4-methyl salicylic acid) and [Ln(HL2)L2·2MeOH]n (Ln = Eu (8), Tb (9), Gd (10), La (11), H2L2 = 3-hydroxy-2-naphthoic acid) were synthesized based on two ligands, and five of them (1-4 and 8) were characterised by X-ray single crystal diffraction. The powder X-ray diffraction patterns (PXRD) of complexes showed that 1-7 are isostructural, 8-11 are isostructural. Furthermore, 1 was characterised by Fourier transform infrared (FT-IR), thermogravimetric analysis (TGA), differential thermal analysis (DTA), elemental analysis (EA), one and two photon luminescence were investigated in detail. © The Royal Society of Chemistry 2013.